MANAJEMEN PENDIDIKAN ISLAM DI TENGAH ARUS DISRUPSI: REFLEKSI KONSEPTUAL UNTUK REPOSISI STRATEGIS LEMBAGA ISLAM DI KEDIRI - Itsna, Itsna Rusydiana (Education Reserach Center, 2025)
The era of disruption, characterized by rapid technological development and shifts in socio-cultural patterns, requires Islamic educational institutions to reassess and adjust their management strategies to maintain relevance. This library research adopts a qualitative approach to analyze how Islamic education management can effectively respond to disruptive changes, with a particular focus on Kediri, a region known for its strong pesantren and madrasah traditions. The findings indicate persistent challenges, including limited digital integration, organizational resistance to change, and weak strategic leadership. Nevertheless, emerging initiatives such as digital-based learning, participatory governance, and value-driven innovation demonstrate promising adaptive potential. This study proposes a strategic repositioning framework rooted in Islamic principles such as amanah (trust), musyawarah (deliberation), and ihsan (excellence), integrated with contemporary management concepts. The model emphasizes three key dimensions: strengthening fundamental Islamic values, implementing adaptive technology-based management, and building external collaboration with educational, industrial, and digital communities. The integrative-adaptive approach positions Islamic educational institutions not only as preservers of tradition but also as dynamic agents of innovation. These findings contribute theoretically to the discourse on Islamic education management and provide practical insights for institutional leaders in pursuing sustainable transformation amidst global educational disruption